Understanding Azure monitoring : includes IaaS and PaaS scenarios - Chakraborty, Bapi; Kathikeyan, Shijimol Ambi (Apress, 2019)
Explore the architectural constructs of Azure monitoring capabilities and learn various design and implementation aspects for complex use cases. This book covers the different scenarios in a modern-day multi-cloud enterprise and the tools available in Azure for monitoring and securing these environments. Understanding Azure Monitoring starts by discussing the rapid changes happening in the cloud and the challenges faced by cloud architects. You will then look at the basics of Azure monitoring and the available tools, including service level agreements (SLAs), auditing, and security. Next, you will learn how to select the best tools for monitoring, operational strategy, and integration with on-premises SIEM systems. You'll work through some scenario-based examples to monitor the workload and respond to failures. Here, you will monitor a simple web application on Azure, a multi-region web application, and applications that include PaaS and IaaS services. Towards the end of the book, you will explore monitoring in DevOps and see why it is important to be aware of continuous changes. You will: Work with Azure IaaS and PaaS resources and monitoring and diagnostics capabilities Discover how the operational landscape changes on Azure Look at cloud-only and on-premises hybrid integration Study architectural constructs for design and implementation.